(untitled) (TUTA Journal, 2022)
Organic farming is basically known as the nature supporting farming done by the use of local resources. Many people have also misconception and confusion regarding this topic. There are several motivating factors for any organic farmers for doing organic farming and the motivators vary from farmers to farmers. The general purpose of the study was to know the motivating factor for doing organic farming in one of the ward of municipality Rangeli, Morang. Descriptive research design is used in this study. Survey is conducted and questionnaire was asked by face to face and telephonic interview for collecting the needed data. Thirteen organic farmers are taken as sample for this study. Random and convenient sampling method of non-probability sampling is used in this survey. Both the primary and secondary sources of data are used in this study. It was found that some of the motivating factors for farmers to do organic farming were higher profit factor, public health consciousness, environmental protection and ecological balance. Most of them accepted they were doing organic farming because of public health consciousness which was followed by the profit factor. It has contributed towards balancing the ecological chain, helps in generating profit for farmers and has done overall welfare to the society and nation. The study recommends the organic farmers to focus on the public health, environment and ecological balance as well as to satisfy their need for profit. They should focus on fulfilling the increasing demand for organic products. The government should give support the organic farmers and also encourage the female participation with effective formulation and proper implementation of better plans and policies.